MOONLIGHTING BEHAVIOURS OF PUBLIC SECTOR WORKFORCES AND THEIR EFFECT ON ORGANISATIONAL COMMITMENT - Ufomba, Ruth E.; Monyei, Francis Ezieshi; Ebona, Francisca C.; Achuncho, Sonia L.; Kelvin-Iloafu, Lovlyn Ekeowa; Ukpere, Wilfred Isioma (Veredas do Direito, 2025)
In emerging economies, the growing prevalence of moonlighting behaviour among public sector workers raises critical questions about its impact on organisational commitment or job performance. As such, this study investigates the prevalence, motivations, and implications of moonlighting among public sector workforces in Lagos State, Nigeria. The research employs a quantitative approach using structured questionnaires administered to 400 randomly selected public servants across various ministries and government agencies. Data were analysed using descriptive statistics, correlation, regression, and ANOVA tests. Findings reveal a significantly positive association between moonlighting and organisational commitment. Thus, it was concluded that the behaviours of moonlighting by public sector staff significantly affect their job performance and have an impact on organisational commitment, while raising ethical concerns.